Proposal to enhance public service ethics in the public sector in Saudi Arabia - bin Duraib, Bandar bin Abdul Rahman (Arab Journal for Sciences and Research Publishing, 2016)
Objective: The aim of this study was to try to build a model can be taken to strengthen and activate the ethics of public service in the public sector in Saudi Arabia. Methodology: In light of the nature of the study and the objectives it seeks to achieve, the researcher used the descriptive method with its documentary inlets and the introduction of social survey. This study was conducted in 2015 where this study adopted in its method, the method of office research through the knowledge and research of various sources of books, studies, research and scientific letters, including what was written about the ethics of public office in Saudi Arabia, and some of which was written about The ethics of public function in the Arab world, as well as reference to some foreign sources. Results: The public sector in Saudi Arabia, like many third world countries, suffers from a decline in the levels of job ethics among employees, despite the efforts made by the Saudi government to reduce this, but these efforts are still below the level of hope. This requires officials to consider developing effective solutions to this dilemma at all levels. Conclusion: The public sector in Saudi Arabia continues to suffer from low levels of public office ethics and efforts must be combined at all levels in the country in order to support and consolidate this ethics among citizens in general and public sector employees in particular.
Keywords: public employee; public sector; public office ethics; civil service; administrative corruption